Macroeconomic implications of downward wage rigidities - Mirko Abbritti; Stephan Fahr (European Central Bank (ECB), 2011)
Growth of wages, unemployment, employment and vacancies exhibit strong asymmetries between expansionary and contractionary phases. In this paper we analyze to what degree downward wage rigidities in the bargaining process affect other variables of the economy. We introduce asymmetric wage adjustment costs in a New-Keynesian DSGE model with search and matching frictions in the labor market. We find that the presence of downward wage rigidities strongly improves the fit of the model to the skewness of variables and the relative length of expansionary and contractionary phases even when detrending the data. Due to the asymmetry, wages increase more easily in expansions, which limits vacancy posting and employment creation, similar to the flexible wage case. During contractions nominal wages decrease slowly, shifting the main burden of adjustment to employment and hours worked. The asymmetry also explains the differing transmission of positive and negative demand shocks from wages to inflation. Downward wage rigidities help explaining the asymmetric business cycle of many OECD countries where long and smooth expansions with low growth rates are followed by sharp but short recessions with large negative growth rates.
Keywords: E31; E52; C61; 330; asymmetric adjustment costs; downward wage rigidity; Labor market; non—linear dynamics; Unemployment